Factors affecting breeding habitat selection in a cliff-nesting peregrine Falco peregrinus population - M. Brambilla; D. Rubolini; F. Guidali (Journal of Ornithology, 2006)
We studied factors affecting breeding habitat selection in a population of cliff-nesting peregrines Falco peregrinus across multiple spatial levels (cliff site, cliff context and land-use of the surrounding landscape), over a 2,100 km2 study area in the Alps (Italy and Switzerland). We detected 30 breeding pairs (density: 1.43 territorial pairs/100 km2), whose territories were uniformly distributed over the study area. We compared 15 habitat features characterising occupied cliffs and 30 randomly selected unoccupied cliffs by means of stepwise forward logistic regression and hierarchical partitioning. The logistic regression analysis showed that occupied cliffs were longer (horizontal length), steeper, and had a greater extension of urban areas in the surrounding landscape compared to non-occupied cliffs. The model had a discrimination ability of 0.95. Hierarchical partitioning indicated that the logistic regression model was appropriate. Neither the distance of cliffs to the nearest site occupied by a potential competitor and predator, the eagle owl Bubo bubo, which occurred at a low density (0.67 pairs/100 km2), nor the distance to the nearest site occupied by peregrines had any effect on the cliff suitability model. Therefore, habitat selection in cliff-nesting peregrines was mainly influenced by cliff site features and surrounding landscape characteristics, whereas the proximity to conspecifics and to an intraguild predator had no apparent effects on peregrine settlement in our study population.